Phototropism in gametophytic shoots of the moss Physcomitrella patens - Bao, Liang (Plant Signal Behav, 2015)
Shoot phototropism enables plants to position their photosynthetic organs in favorable light conditions and thus benefits growth and metabolism in land plants. To understand the evolution of this response, we established an experimental system to study phototropism in gametophores of the moss Physcomitrella patens. The phototropic response of gametophores occurs slowly; a clear response takes place more than 24 hours after the onset of unilateral light irradiation, likely due to the slow growth rate of gametophores. We also found that red and far-red light can induce phototropism, with blue light being less effective. These results suggest that plants used a broad range of light wavelengths as phototropic signals during the early evolution of land plants.